Effect of long haul travel on maximal sprint performance and diurnal variations in elite skeleton athletes. Issue 9 (1st May 2007) - Bullock, Nicola; Martin, David T; Ross, Angus; Rosemond, Doug; Marino, Frank E
Abstract : Objective: To quantify the impact of eastward long haul travel on diurnal variations in cortisol, psychological sensations and daily measurements of physical performance. Methods: Five elite Australian skeleton athletes undertook a long haul eastward flight from Australia to Canada (LHtravel ), while seven elite Canadian skeleton athletes did not travel (NOtravel ). Salivary cortisol was measured on awakening, 60 min and 120 min after awakening. Psychological sensations were measured with a questionnaire, and maximal 30 m sprints were performed once a day between 09:30 and 11:00 h local time. Results: Compared with baseline, average (SD) resting salivary cortisol decreased by 67% immediately after long haul travel (23.43 (5.71) nMol/l) (mean±90% confidence interval) in the LHtravel group (p = 0.03), while no changes were found in the NOtravel group (p = 0.74). There were no significant differences in 30 m sprint time between baseline and post-flight tests in the LHtravel group (p>0.05). The LHtravel group perceived themselves as "jet lagged" for up to 2 days after the flight (p = 0.01 for both midday lunch and evening dinner). Conclusions: Despite a distinct phase change in salivary cortisol rhythmicity and the athletes perceiving themselves as "jet lagged", minimal disturbances in "one-off" maximal sprinting ability between 09:30 and 11:00 h local time were seen in a group of elite skeleton athletes after long haul eastward travel from Australia to Canada.